Legislation targeting head shops selling new psychoactive substances and changes in drug‐related psychiatric admissions: A national database study. Issue 1 (4th April 2019) - Smyth, Bobby P.; Daly, Antoinette; Elmusharaf, Khalifa; McDonald, Conor; Clarke, Mary; Craig, Sarah; Cullen, Walter
Abstract : Aim: New psychoactive substance (NPS) use can negatively impact mental health and may result in drug‐related psychiatric admissions (DRPA). Irish youth reported very high rates of NPS use by international standards, the most common being synthetic cannabinoids and cathinones. This occurred in the context of a rapid expansion in specialist high street shops, called head shops, selling NPS in 2010. Government responded to public protests about head shops by enacting legislation in May and August 2010 to end this trade. Many academics argued that such actions were futile. We sought to determine if changes in head shop activity coincided with changes in DRPA. Method: The national database on psychiatric admissions was examined focusing on young adults admitted from 2008 to 2012. Joinpoint regression analysis was utilized to examine for the presence of trend changes in DRPA. Results: The monthly rate of DRPA was higher in 2010 than 2008, 2009 and 2012 ( P  < 0.01). Joinpoint regression analysis identified a significant downward trend change which occurred in July 2010 (95% CI Feb 2010 to April 2011). Young males aged 18 to 24 years showed evidence of greatest change, DRPA falling by 1.4% per month (95% CI 0.7 to 3.7% decline) from May 2010 to December 2012. Conclusions: Cessation of NPS sale by head shops coincided with a reversal in the upward trend of DRPA, this change being most evident in young men. While correlation does not imply causation, legislation which successfully targets the sale of NPS may result in reduced drug‐related mental disorders.